Pengaruh Bobot Isi Tanah Terhadap Sifat Fisik Tanah Dan Perkecambahan Benih Kacang Tanah Dan Kedelai (Effect Of Soil Bulk Density On Soil Physical Properties And Seed Germinations Of Peanut And Soybean) - Oteng Haridjaja; Yayat Hidayat; Lina Siti Maryamah (Institut Pertanian Bogor, 2010)
Soil physical properties can affect to seed germination and plant growth. Soil compaction will degrade soil physical properties which in term will affect to root penetration and developement in the soil. The improvements of soil physical properties is required to ensure seed germination and plant growth such as treatment to maintain soil bulk density is quite low. The purpose of this research is to study the influence of soil compaction (soil bulk density) to soil physical characteristics and seed gemination of peanuts and soybean. This research used Jasinga Podsolik soil, conducted at Soil Physical Laboratory, Departement of Soil Science and Land Resources, Faculty of Agriculture IPB. and Greenhouse of Center of Biological Resources and Biotechnology, Research and Community Service Agency, IPB (March-November 2009). Completed random design was used as experimental design and Duncan's Multiple Range Test (DMRT) was used to identify the effect of treatment. The bulk density result of the research showed that the increasing of soil bulk density (soil compaction) had significantly affect on pF curves, permeability rate, and soil resistance before or after planting. For peanuts, soil compaction significantly affect to plant height and root length. Soil compaction did not significantly affect of stem diameter, number of leaves, canopy or root biomass. For soybean, the influence of soil compaction did not significantly affect just only on plant height. Stem diameter, number of leaves, root length or root and canopy biomasses were not affected by soil compaction.